N,S-Co-doped TiO2 Nanophotocatalyst: synthesis, electronic structure and photocatalysis - Sathish, M.; Viswanath, R. P.; Gopinath, Chinnakonda S. (Journal of Nanoscience and Nanotechnology, 2009)
N,S-co-doped anatase-phase TiO2 (N,S-TiO2) nanophotocatalysts were prepared from either benzothiazoline or aminothiol with titanium isopropoxide followed by a systematic thermal decomposition. The chemical nature of S and N in N,S-TiO2 have been identified by XPS to be sulfate and NO-like, respectively. A significant band broadening and red-shift in the UV-visible absorption spectrum of N,S-TiO2 suggests a band gap reduction compared to TiO2. A maximum band-gap narrowing of 0.22 +/- 0.02 eV was observed on N,S-TiO2. Higher energy width observed on N,S-TiO2 is in contrast to 0.13 eV from N-doped TiO2 indicating the sulfate-like species might play a major role in narrowing the band-gap to a Higher level. It is confirmed that the oxidation of N and S to NO and SO42- occurs in the final stage of preparation of N,S-TiO2, during calcination in air. It is predicted that the oxygen associated with sulfate and NO structural features could be crucial in bringing down the energy gap and red shift in optical absorption and the role of sulfur is to facilitate the above. Photocatalytic decomposition of methylene blue has been carried out on N,S-TiO2 shows higher activity than the commercial TiO2 in the visible region. However, sulfate species seems to enhance the activity of N,S-TiO2 marginally compared to N-TiO2, and possible suggestions are given to improve the same.
Keywords: nitrogen; Photocatalyst; Sulfur; TiO2; Visible Light Absorption